Behavioral effects of sports experience on the physical activity of students in the process of studying at a higher educational institution - Ponimasov O.E. ,; Belyakova M.Yа. ,; Saiganova E.G. ,; Mironov A.O. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the dependence of students' motor activity during university studies on previous experience in sports activities. Methods and structure of the study. The data was collected through an anonymous survey in which 165 students (75 young men and 90 girls) participated. The questionnaire included 52 questions aimed at studying the experience and duration of a particular sport, the level of physical activity, the main reasons for the decrease in motivation to engage in physical education, as well as participation in mass sporting events during the first academic semester. Results and conclusions. Upon admission from a school to a higher education institution, there is a decrease in the number of young people involved in physical culture and sports activities. An important aspect of motivating students for sports activities is taking personal interests into account when planning sports events.